Baby-Naming Rituals and Shamanism in Three Icelandic Family Sagas with Cross-Cultural Comparisons - Beyer, Emily Hoffman, 1979- (2017)
This thesis explores baby-naming traditions in connection with shamanism in three Íslendingasögur, Egils saga Skallagrímssonar, Laxdæla saga, and Gísla saga Súrssonar, as well as others. It argues that the baby-naming rituals seen in those sagas are rooted in shamanistic social practices. A cross-cultural analysis of baby-naming traditions in Sámi, Icelandic, and Greenlandic Inuit communities from post-Reformation accounts supports this claim. This comparison of the sagas with cultural practices creates a dialogue between literature, cultures, and contexts and provides a path of inquiry into the Old Norse depictions of a remembered pagan and early Christian culture around birth. Old Norse texts and post-Reformation accounts suggest that baby naming in Icelandic communities to some degree is comparable to both Sámi and Greenlandic Inuit traditions of coupling babies with dead relatives through naming. Babies’ namesakes functioned along with other supernatural aides to provide societal advantage and prestige, as well as spiritual support for individuals’ shamanic development. Furthermore, depictions of namesakes in the sagas create parallel structural units, providing insight into oral traditions or kinship storytelling patterns. This research on baby-naming rituals and the roles of shamans or others with shaman-like skills is a beginning step in our understanding of the intricacies of birth and naming practices in the Old Norse corpus. Í þessari ritgerð kanna ég nafnahefðir í tengslum við sjamanisma meðal annars í íslendingasögunum Egils sögu Skallagrímssonar, Laxdæla sögu og Gísla sögu Súrssonar. Ég færi rök fyrir því að nafngiftir barna í þessum sögum eiga rætur að rekja til sjamanismahefða. Greining þvert á menningarheima Sama, Íslendinga og Grænlendinga í textum skrifuðum eftir siðaskipti styður kenninguna. Með þessum samanburði á Íslendingasögur og menningarhefðir myndast „samtal” á milli bókmennta, menningarheima og aðstæðna sem gefur okkur tækifæri að rannsaka nánar þær lýsingar á fæðingarsiðum frá tímum ...